The Effect of Cylinder Head Face Cutting on The Diesel Engine Performance &Exhaust Emission - Hussein, Mohanad Hamzah (Nahrain University College of Engineering Journal, 2017)
The aim of this study is to know the effect of remove layer from head cylinder thickness on engine performance and exhaust emission. In this experiment used four stroke four cylinder diesel engine connect to the hydraulic dynameters , The experiment was conducted at a fixed engine speed of 1500 RPM and variety load with two type of cylinder head M0(original head cylinder thickness and for this type the Compression ratio equal 18) and M1 (remove 1mm from head cylinder thickness and the Compression ratio will be increase and become Cr=19) and.brake specific fuel consumption , brake thermal efficiency and brake power were examined , M1 produce better engine output such as: brake thermal efficiency increase by 0.87%,Bp increase by 0.50%, CO2 increased by 18% while the NOx increased around 1.37% in the other hand found brake specific fuel consumption decrease by 0.75% and monoxide carbon decrease by 33% when compared with cylinder head type M0.